2005
DOI: 10.1002/ejic.200400976
|View full text |Cite
|
Sign up to set email alerts
|

Hemilabile Thioether Ligands Based on Pyrimidine and/or Pyridine Derivatives that Interconvert between N,S‐ and N‐Coordination in Congested Ruthenium(II) Complexes

Abstract: The thioether ligands L [L = 2-pyridylmethyl 2Ј-pyridyl sulfide (L 1 ), 2-pyridylmethyl 2Ј-pyrimidyl sulfide (L 2 ) and 2-pyr-investigations show that these potentially tridentate ligands act as N,S-bidentate species, to form a five-membered RuSCCN(Ru-N) ring, and in certain cases, as N-monodentate species coordinated to the ruthenium through the 2-pyridylmethyl group. The N,S-chelated species contain chiral sulfur and ruthenium atoms with (R) and (S), and Δ and Λ configurations, respectively. Two invertomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…These data indicate that dps, 4mdps and 5mdps act as N,N-chelate ligands. [12][13][14][15][16][17] These findings were confirmed by subsequent 1 H and 13 C NMR spectroscopic studies.…”
Section: Synthesis Of the Compoundssupporting
confidence: 83%
See 4 more Smart Citations
“…These data indicate that dps, 4mdps and 5mdps act as N,N-chelate ligands. [12][13][14][15][16][17] These findings were confirmed by subsequent 1 H and 13 C NMR spectroscopic studies.…”
Section: Synthesis Of the Compoundssupporting
confidence: 83%
“…[4,[6][7][8]11] Some years ago, studying the coordination chemistry of thioethers based on pyridine or pyrimidine, we found that these usually N,N-bidentate donors [12] often show N,S che-lation towards congested ruthenium substrates. [13][14][15][16][17] The resultant complexes display dynamic stereochemical rearrangements associated with inversion at the sulfur atom coordinated to the ruthenium, [14] the restricted rotation of the pendant ring [15] and the exchange between different coordination modes. [17] NMR spectroscopic studies by us were performed to elucidate the mechanisms of these processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations